HIBAH SEMUA HARTA KEPADA ANAK ANGKAT (TELAAH KOMPARASI ANTARA KUH PERDATA DAN KHI) - Abdoeh, Nor Mohammad (IAIN Tulungagung, 2020)
One of the ways that human beings use to obtain treasure is grants. The grant process cannot be separated from the limit of the donated property. In reality, many people grant his wealth to his adopted son with all his possessions. It is a matter of the adopted child's position in the law. The purpose of this paper is to explain how the views of the Civil Code and the Islamic Law about grant and that comparation. The approach of this research with normative approach, by investigating whether it is according to the norms that apply. The conclusion of this research, that the rules of grant in the Civil Code and KHI actually have similarities and differences. The similarity of the two rules is seen in defining the meaning of the grant, its elements and similarity in judging a qualified person to do the grant. The difference of the rules are both seen in the share of grant distribution. The portion in KHI is a maximum of 1/3. The existence parts and restriction of the treasures in the grant is nothing but to protect from the tendency of the benefactor to ignore their family. While in the Civil Code based on Legitime Portie